Tree Community Structure and Composition of a One-Hectare Permanent Plot in the Montane Zone of Mount Kerinci, Kerinci Seblat National Park, Jambi - Endah Sulistyawati; Taufikurrahman Nasution; Dian Rosleine; Dian Cahyana Putra (Institute for Research and Community Services (LPPM) ITB, 2018)
Information on tree community structure and composition is needed in forest management and restoration. These data can be obtained using a permanent plot for studying forest dynamics, including species-specific characteristics. These characteristics are useful in the identification of native species for commercial and restoration purposes. This study aimed to describe the tree community structure and composition of a one-hectare permanent plot in the montane zone of Mount Kerinci. Data collection was conducted from July to August 2016 on Mount Kerinci, Jambi. A plot was established at 2,182-2,258 m above sea level and subdivided into 100 subplots. All trees â‰¥ 10 cm DBH were tagged and measured. Twenty-eight species, 18 genera, 20 families, 570 individuals and Shannon index 2.89 were identified. Most of the potential species richness was covered on the research site. Syzygium lineatum was the species with the highest importance value and Myrtaceae had the highest family importance level. The study area was dominated by slow growing species that characterize primary forests. The population structure indicated a good capacity of forest regeneration, while the vertical structure formed a stratification consisting of three strata. The dominant large trees and 5 hyperdominant trees according to total biomass contribution were identified. These species are an important priority in forest management and restoration.